tìm điều kiện xác định của P và rút gọn biểu thức P P= [ ( √x /-1+√x) – (1/x- √x) ] / [ (1/1+ √x )+ (2/x-1)

Question

tìm điều kiện xác định của P và rút gọn biểu thức P
P= [ ( √x /-1+√x) – (1/x- √x) ] / [ (1/1+ √x )+ (2/x-1)

in progress 0
Athena 5 tháng 2021-07-15T11:42:20+00:00 1 Answers 5 views 0

Answers ( )

    0
    2021-07-15T11:43:40+00:00

    Đáp án:

    \(P = \dfrac{{x – 1}}{{\sqrt x }}\)

    Giải thích các bước giải:

    \(\begin{array}{l}
    DK:x > 0;x \ne 1\\
    P = \left( {\dfrac{{\sqrt x }}{{\sqrt x  – 1}} – \dfrac{1}{{x – \sqrt x }}} \right):\left( {\dfrac{1}{{1 + \sqrt x }} + \dfrac{2}{{x – 1}}} \right)\\
     = \left[ {\dfrac{{x – 1}}{{\sqrt x \left( {\sqrt x  – 1} \right)}}} \right]:\left[ {\dfrac{{\sqrt x  – 1 + 2}}{{\left( {\sqrt x  – 1} \right)\left( {\sqrt x  + 1} \right)}}} \right]\\
     = \dfrac{{\left( {\sqrt x  – 1} \right)\left( {\sqrt x  + 1} \right)}}{{\sqrt x \left( {\sqrt x  – 1} \right)}}.\dfrac{{\left( {\sqrt x  – 1} \right)\left( {\sqrt x  + 1} \right)}}{{\sqrt x  + 1}}\\
     = \dfrac{{\sqrt x  + 1}}{{\sqrt x }}.\left( {\sqrt x  – 1} \right)\\
     = \dfrac{{x – 1}}{{\sqrt x }}
    \end{array}\)

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )